Employment protection, product market regulation and firm selection - Winfried Koeniger; Julien Prat (Institute for the Study of Labor (IZA), 2006)
This paper analyzes the effect of labor and product market regulation in a dynamic stochastic equilibrium with search frictions. Modeling multiple-worker firms allows us to distinguish between the exit-and-entry (extensive) margin, and the hiring-and-firing (intensive) margin. We characterize analytically how both margins depend on regulation before we calibrate the model to the US economy. We find that firing costs matter most for the intensive margin. Fixed or set-up costs in the product market instead alter primarily the behavior of firms at the extensive margin. Moreover, we find important interactions between the policies through firm selection. Finally, the opposite effect of product and labor market regulation on job turnover rationalizes the empirically observed similarity of turnover rates across countries.
Keywords: E24; J63; J64; J65; 330; firing cost; product market regulation; firm selection; firm turnover; job turnover; Kündigungsschutz; Regulierung; Arbeitsmarktpolitik; Arbeitsmobilität; Markteintritt; Theorie